2015
DOI: 10.4018/ijcbpl.2015040103
|View full text |Cite
|
Sign up to set email alerts
|

Individual Characteristics and Hacking, Piracy, Online Gambling and Pornography Use among Students

Abstract: In this study, 441 Universiti Teknologi Malaysia students participated as respondents. Through a questionnaire respondents were asked how frequently they engage in specific behaviors, including hacking, using pirated software, music and movies in addition to use of gambling and pornography sites. The aim was to investigate which individual characteristics including age, gender, religion, citizenship, level of education, ego strength and locus of control are among determinants of these behaviors. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This differs from their actual behaviour, as intention refers to the willingness or desire to act, while behaviour pertains to the actual action individuals take (Eisend, 2019). The second strand, on the other hand, examines endusers who engage in music piracy (for instance, Gunter et al, 2010;Jafarkarimi et al, 2015;Popham, 2011;Rochelandet & Le Guel, 2005). Previous research on music piracy has considered various factors, that can be classified into four major groups: (1) socio-demographic characteristics, (2) knowledge and sanctions, (3) social learning, and (4) technological accessibility.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from their actual behaviour, as intention refers to the willingness or desire to act, while behaviour pertains to the actual action individuals take (Eisend, 2019). The second strand, on the other hand, examines endusers who engage in music piracy (for instance, Gunter et al, 2010;Jafarkarimi et al, 2015;Popham, 2011;Rochelandet & Le Guel, 2005). Previous research on music piracy has considered various factors, that can be classified into four major groups: (1) socio-demographic characteristics, (2) knowledge and sanctions, (3) social learning, and (4) technological accessibility.…”
Section: 2mentioning
confidence: 99%
“…This provides a better understanding of music piracy by revealing end-users' music consumption behaviour. Finally, this study also contributes to the limited number of empirical studies by using survey data from a general population, rather than focusing on a specific group of individuals (for instance, Chiou et al, 2005;Coyle et al, 2009;Gunter et al, 2010;Holt & Morris, 2009;Jafarkarimi et al 2015;Liu, 2009;Lysonski & Durvasula, 2008), thereby providing a more comprehensive view of the issue. Overall, this study sheds light on consumers' perspectives on music piracy, and its research findings provide valuable insights for stakeholders in the music industry and policymakers to reduce the prevalence of this practice.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in the study of Ali et al [1] were mainly Malays, with up to 90.8%, whereas this study recruited 82% Chinese and only 8.6% Malay participants. Moreover, Jafarkarimi et al [39] affirmed that Malaysian college students confirmed that pornography use is affected by religion where Muslims are less likely to view pornography than non-Muslims. Therefore, cultural factors across ethnic and religious backgrounds could explain the differences between perceived realism and pornography addiction.…”
Section: Plos Onementioning
confidence: 99%
“…A study reported that teenagers turned their skills into illegal practices, such as using mobile phones for cheating by downloading online sources and plagiarize others' work without acknowledgement [10]. Besides, in a study conducted in a local university in Malaysia, the authors expressed their concern with the fact that students are using their digital skills to conduct unethical activities, which are hacking (15%), movie piracy (67%) and gambling (7%) [11].…”
Section: Eai Endorsed Transactions On Pervasive Health and Technologymentioning
confidence: 99%